Study and Practice on Test Methodology of Link Aggregation Based on LACP - Liang Guo (Dianxin kexue)
LACP is a link aggregation technologies which has been widely deployed in network architecture,it is considered as a low cost but effective way to increase bandwidth and improve stability of network as well.LACP technologies were introduced,common cases in real network were analyzed,and a solution on LACP validation in lab environment was put forward.Key points on LACP functional and performance validation were provided,and these were implemented in lab environment by using Ixia tester to emulate protocols and traffics over LACP.